Hydroxamate-Based Histone Deacetylase Inhibitors as Potential Mediators to Induce Dentine Regeneration by Human Dental Pulp Cell - Indrani Sulistyowati; Teerawat Sukpaita; Chalida Nakalekha Limjeerajarus; Ruchanee Salingcarnboriboon Ampornaramveth; Ruchanee Salingcarnboriboon Ampornaramveth (Frontiers Media S.A., 2021)
Human dental pulp cells (hDPCs) have shown their plasticity when treated with the hydroxamate-based histone deacetylase (HDAC) inhibitor members, Trichostatin A (TSA), and suberoylanilide hydroxamic acid (SAHA). However, a comparison of their potency to stimulate odontoblast-like differentiation and mineralization has not been reported. The aim of our study was to confirm and compare these TSA and SAHA effects. Primary hDPCs cultured with/without various TSA or SAHA concentrations were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT), ALP activity, alizarin red staining, and scratch wound healing assays. The inhibitory effect of TSA and SAHA on inhibiting the activity of HDAC was evaluated by HDAC activity assay. Odontoblast-related gene expression was determined using RT-qPCR. The MTT assay indicated that TSA or SAHA did not affect hDPC viability. TSA or SAHA treatment-induced odontoblast-like differentiation as evidenced by a significant increase in alkaline phosphatase activity and mineral deposition after 400 nM TSA or 1 μM SAHA treatment. A significant increase in nuclear factor I C, kruppel like factor 4, dentin matrix acidic phosphoprotein 1, dentin sialophosphoprotein, collagen type I alpha 1 chain, alkaline phosphatase (ALPL), integrin-binding sialoprotein, bone gamma-carboxyglutamate protein, vascular endothelial growth factor A, and cyclin-dependent kinase inhibitor 1A gene expression analyzed by RT-qPCR, at 24, 72 h, 7, and 10 days of treatment. The activity of HDAC in hDPCs culture was significantly inhibited after 72 h TSA and SAHA treatment. The scratch wound healing assay displayed enhanced cell migration at 72 h after TSA or SAHA treatment. Our findings demonstrated that TSA and SAHA have similar stimulatory effects in inducing HDPC odontogenic differentiation and mineralization and propose another potential use of TSA and SAHA to promote dentin regeneration.